Electromagnetic excitation of PEC slotted cones by elementary radial dipoles – a semi-inversion analysis - Semenova, E. K.; Doroshenko, V. A. (IEEE, 2008)
This paper presents a novel method that is based on the use of the Kontorovich-Lebedev integral transform and the semi-inversion technique, developed for building the efficient and accurate numerical solutions to the boundary-value problems of electromagnetic wave scattering by 3D coaxial slotted cones.
Keywords: Electromagnetic excitation; semi-inversion analysis